Peran Kelompok Tani dalam Usahatani Padi Sawah (Oryza sativa L) di Desa Belatu Kecamatan Pondidaha Kabupaten Konawe - Arini, Ade Ayusri; Arimbawa, Putu; Abdullah, Sukmawati (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This study aims to determine the role of farmer groups in lowland rice farming in Belatu Village, Pondidaha District, Konawe Regency. This research was conducted in November 2016-March 2017. Determination of the sample using cluster random sampling is by taking 25% of the population so that the number of samples is 27 people. Analysis of the data used is the interval formula. The results showed that the role of farmer groups in wetland farming in Belatu Village, Pondidaha District, Konawe District was dominantly in the medium category. then the role of farmer groups as the dominant learning class is in the high category. While the role of farmer groups as a vehicle for cooperation and dominant production units is in a low category.